"IN SEARCH OF RASTRELLI ...". (RESTORATION OF ST. ANDREW'S CHURCH IN 2009-2020) (City: History, Culture, Society, 2021)
At the end of 2020, St. Andrew's Church in Kyiv became accessible to the public after a long restoration (2009-2020). The philosophy of the restoration work of this decade was subordinated to the idea of "Rastrelli's return". Besides, there is a specific "longevity" - because, during the previous large-scale restoration in 1979-88, the authentic look (according to the collection of Rastrelli's original drawings) was returned to the exterior of the church (especially the domes). Rastrelli is also the author of the project of interior decoration of St. Andrew's Church. Therefore, all the works were aimed at restoring the most authentic look of the temple. They were performed by the restorers of the research and restoration workshop of the National Reserve "Sophia of Kyiv" and LLC "EXTERIOR-BUDSERVICE" (general contractor). Unofficially, the work was divided into four blocks with eloquent names - "Metal", "Stone", "Wood" and "Painting".
Keywords: : St. Andrew's Church; restoration; Kyiv; Francesco Bartolomeo Rastrelli